Field Static Load Tests of Post-Grouted Piles under Various Failure Conditions. (13th August 2020) - Zhou, Jialin; Zhang, Jianwei; Wang, Yuzhuo; Oh, Erwin
Abstract : In practice, inappropriate test set-up and design will result in pile eccentricity, reducing pile bearing capacity. Also, inappropriate piling will reduce the strength of the upper part of concrete. These pile elements under inappropriate design and construction are easy to be overlooked since they are invisible. Because the research focuses on the pile failure behaviour under different conditions, this paper aims to determine the outcomes of pile foundation under eccentric loading, pile with inadequate concrete strength, and pile with punching failure. Four concrete piles were cast, and compressive static load tests (SLTs) were performed. The top part of the first pile was cast with inadequate concrete strength. The other two piles were cast with achieved concrete strength; however, one of these applied with eccentric loading. The third pile was the standard pile, and the fourth pile was tested until punching failure occurred. For the fourth pile, the T-Z method was used for determining the failure characteristics. It is discovered that, for the pile with inadequate concrete strength, the cracks occurred at the pile head, and the concrete crushed at 0.9–1.2 m below the ground; for the pile suffering eccentricity, the partial concrete crushed, and the concrete from the opposite side suffered tension fracture; for the pile suffering punching failure, the crack on the soil extends up to 50 mm. Traditional result presentations and interpretations were also provided. Furthermore, it was found that, for the pile suffering punching failure, the shaft resistance increased as the loads increased, and after the loading achieved the maximum resistance, the loading transferred to the pile tip and finally led to the destruction of the pile-soil system.